Use of Habek Mint (Mentha longifolia) in Broiler Chicken Diets - Al-Ankari, A.S.; Zaki, M.M.; Al-Sultan, S.I. (International Journal of Poultry Science, 2004)
An attempt has been conducted to evaluate the effect of habek on performance and immunity of broiler chickens. Five levels of whole habek, 0, 25, 100, 150 and 200 g/kg were incorporated into basal diet of 125 broilers for 5 weeks. The results of the study showed that including 150 g/kg habek into broiler diet make a significant improvement in the mean body weight, daily average gain, feed intake and food conversion ratio. However, in another experiment, habek had no effect on the immune response of the birds against Newcastle disease virus live vaccine when a group of 25 birds was given basal diet supplemented with 150 g/kg habek compare to that fed basal diet only.